A comprehensive assessment of Next‐Generation Sequencing variants validation using a secondary technology. Issue 7 (4th June 2019) - Zheng, Jianchao; Zhang, Hongyun; Banerjee, Santasree; Li, Yun; Zhou, Junyu; Yang, Qian; Tan, Xuemei; Han, Peng; Fu, Qinmei; Cui, Xiaoli; Yuan, Yuying; Zhang, Meiyan; et al.
Abstract: Background: Recently, increasing innovations improved the accuracy of next generation sequencing (NGS) data. However, the validation of all NGS variants increased the cost and turn‐around time of clinical diagnosis, and therefore limited the further development of clinical applications. We aimed to comprehensively assess the necessity of validating NGS variants. Methods: Validation data of 7, 601 NGS variants involving 1, 045 genes were collected from 5, 190 clinical samples and sequenced by one of five targeted capture panels and two NGS chemistries, respectively. These genes and variants were widely distributed in 24 human chromosomes and mitochondrial genome. Variants validation was firstly processed by Sanger sequencing. If validation results were unavailable or inconsistent with NGS calls, another validation test would be performed by mass spectrometry genotyping. Results: A total of 6, 939 high quality NGS variants with ≥35 × depth coverage and ≥35% heterozygous ratio were 100% confirmed by a secondary methodology. 5, 775 heterozygous variants were separated from 760 homozygous variants and 404 hemizygous variants by 80% heterozygous ratio. A total of 1.5% (98/6, 939) of NGS variants were validated by mass spectrometry genotyping. Conclusion: Considering of the above comprehensive assessment, a new variant with high quality from a well‐validated capture‐based NGS workflow can be reported directly without validation. Abstract : This study includes 7601 NGS variants from different samples, target capture panels, and sequence platforms. All the variants were validated by Sanger sequencing and/or mass spectrometry genotyping. 6, 939 high quality NGS variants with ≥35× depth coverage and ≥35% heterozygous ratio were 100% confirmed.